Routine habitat switching alters the likelihood and persistence of infection with a pathogenic parasite. (22nd January 2018) - Daversa, David R.; Manica, Andrea; Bosch, Jaime; Jolles, Jolle W.; Garner, Trenton W. J.
Abstract: Animals switch habitats on a regular basis, and when habitats vary in suitability for parasitism, routine habitat switching alters the frequency of parasite exposure and may affect post‐infection parasite proliferation. However, the effects of routine habitat switching on infection dynamics are not well understood. We performed infection experiments, behavioural observations and field surveillance to evaluate how routine habitat switching by adult alpine newts ( Ichthyosaura alpestris ) influences infection dynamics of the pathogenic parasite, Batrachochytrium dendrobatidis ( Bd ). We show that when newts are exposed to equal total doses of Bd in aquatic habitats, differences in exposure frequency and post‐exposure habitat alter infection trajectories: newts developed more infections that persisted longer when doses were broken into multiple, reduced‐intensity exposures. Intensity and persistence of infections were reduced among newts that were switched to terrestrial habitats following exposure. When presented with a choice of habitats, newts did not avoid exposure to Bd, but heavily infected newts were more prone to reduce time spent in water. Accounting for routine switching between aquatic and terrestrial habitat in the experiments generated distributions of infection loads that were consistent with those in two populations of wild newts. Together, these findings emphasize that differential habitat use and behaviours associated with daily movement can be important ecological determinants of infection risk and severity. A plain language summary is available for this article. Abstract : Plain Language Summary